Cartera vencida del GAD del cantón Baba - Calero Muñoz, Ileana Jazmín (2020)
The purpose of this case study is to provide a tool to support the municipal tax administration in its quest to improve self-management income, according to the constitutional mandate, the Municipal Decentralized Autonomous Governments must generate their own financial resources, so that they can be reinvested in social works of benefit to the community, therefore the municipalities of the country must make enormous efforts to increase their self-management income, the maximization of tax revenues must acquire greater relevance in the municipal financial areas, since these represent sources of important income, therefore the objective of this study is to present a proposal based on strategies to improve the collection of taxes for urban, rustic properties, prior to an analysis of the municipal portfolio. To carry out this case, a set of analyzes, document observations and questionnaires were used that work in the municipality, once with the results obtained, it was concluded that the municipality of Baba is deficient in the process of collection of taxes on urban and rustic properties and a lack of tax culture among the inhabitants of the Baba canton.